EFFORTS TO SUPPORT AND EXPAND THE USE OF EDUCATIONAL TECHNOLOGY AS A MEANS OF DELIVERING LEARNING - Retnawati, Elva (Sanata Dharma University Yogyakarta, 2019)
Indonesian government has made improving basic education a priority, and indicated that it sees technology as a way to provide teachers with the means to teach innovative lessons while closing the performance gap between rural and urban schools and between poorer and richer provinces. The role of technology must be aligned with the existing education ecosystem. It should not replace the traditional education system that involves teachers, schools, universities and parents, albeit offering wide range of information and allowing independent learning. Education is not only about learning in school, but also building a character. That is why the role of technology is intended as a tool to support the learning process, to open access, and improve quality. This paper describes the efforts taken by the Indonesian government in supporting and expanding the use of technology in the field of education in Indonesia. The discussions are supported by related research findings and literature.DOI: doi.org/10.24071/ijiet.2019.030112